Etos Kerja Perspektif Al-Qur’an dan Hadis - Khairullah; Aziz Taufiqurrahim; Eko Nur Rohman; Dhiah Rahmawati; Abdul Mufid (Jurnal Multidisiplin Madani, 2022)
The Qur'an and Hadith are Islamic teachings in which there are teachings for charity and work which are prescribed in the sentence "amal as shalihat". The work ethic is one of the seven elements of universal culture, namely the element of "living livelihood system". livelihood system means economic life. Work is an activity carried out by humans in achieving prosperity and if they are lazy, they will fail to get it. Success and failure are the result of their own hard work efforts. In Islam, the characteristics of the work ethic are looking for worldly wealth in a lawful way, not asking for help, providing for family needs and compassion for neighbors. As Rasulullah saw., made work as the actualization of faith and piety. Therefore for a Muslim life is to work. Allah SWT in his word remember that Allah SWT will not change the fate of humans before humans change what is in themselves.